2020
DOI: 10.1155/2020/3469840
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Investigation and In Vitro Verification of Curcumin-Induced HO-1 as a Feature of Ferroptosis in Breast Cancer Cells

Abstract: Ferroptosis is a form of oxidative cell death and has become a chemotherapeutic target for cancer treatment. Curcumin (CUR), a well-known cancer inhibitor, significantly inhibits the viability of breast cancer cells. Through transcriptomic analysis and flow cytometry experiments, it was found that after 48 hours of treatment of breast cancer cells at its half maximal inhibitory concentration (IC50), curcumin suppressed the viability of cancer cells via induction of ferroptotic death. Use of the ferroptosis inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 54 publications
3
66
0
Order By: Relevance
“…Curcumin is a yellow polyphenol compound derived from the turmeric plant, which shows anticancer properties through a variety of mechanisms, including inhibition of tumor proliferation, invasion and metastases, regulation of apoptosis, and autophagy 8 . Recent studies showed that curcumin can treat glioblastoma and breast cancer via regulating ferroptosis 9,10 . However, there seem to be few studies exploring the relationship of ferroptosis and anti‐NSCLC induced by curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin is a yellow polyphenol compound derived from the turmeric plant, which shows anticancer properties through a variety of mechanisms, including inhibition of tumor proliferation, invasion and metastases, regulation of apoptosis, and autophagy 8 . Recent studies showed that curcumin can treat glioblastoma and breast cancer via regulating ferroptosis 9,10 . However, there seem to be few studies exploring the relationship of ferroptosis and anti‐NSCLC induced by curcumin.…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin (CUR) has been widely and safely consumed as a natural food coloring for hundreds of years, and there have been a large number of studies showing its antioxidant, anticancer and anti-inflammatory properties [ 15 , 16 ]. Curcumin can not only effectively remove reactive oxygen species, but also activate antioxidant response elements to inhibit oxidative stress induced by reactive oxygen species [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins involved in iron metabolism, such as transferrin, transferrin receptor 1, and ferroportin, as well as HO-1, have been implicated in the ferroptotic process [ 80 , 91 , 92 ]. Transcriptome Investigation by Li et al, highlighted the role of HO-1 in curcumin-induced ferroptosis [ 93 ].…”
Section: Ho-1 and Ferroptosismentioning
confidence: 99%